Optimasi Peran Desa Adat di Bali melalui Teknologi Informasi - Darmaastawan, Kadek; Oka Saputra, Komang; Ary Esta Dewi Wirastuti, Ni Made (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2021)
Bali is a province in Indonesia known by many countries because of its unique natural and cultural attractions. Balinese traditional village as well known as Desa Adat manage those tourist attractions. Also, Desa Adat has a role in preserving Balinese culture because Desa Adat routinely holds cultural activities such as performing arts and religious ceremonies. The rapid development of technology has brought the internet and smartphones to Desa Adat. These developments have had various positive impacts, for example, the ease of accessing information through the internet and information technology. Desa Adat can utilize information technology to facilitate various activities. However, there are still Desa Adat in Bali that has not utilized information technology therefore, the potential of these villages is not maximized. In the future, there are still many new technologies that will become trends. Therefore, it is not too late for Desa Adat in Bali to utilize information technology. This journal examines previous research on the use of information technology in villages. The purpose of this study is to obtain several aspects of Desa Adat in Bali that can be accommodated by information technology, therefore, the role of Desa Adat in Bali can be optimized.